Ensure Cross‐Connection Control and Backflow Prevention with a Multipoint Approach. Issue 7 (1st July 2015) - Martin, Barb; Ries, Tom
Abstract : Cross‐connections are significant risks to water quality and public health. Utilities can help prevent distribution system contamination through proactive cross‐connection control measures.